2009
DOI: 10.1111/j.1476-5381.2009.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐stimulated, transcription‐independent release of annexin A1 by cochlear Hensen cells

Abstract: Background and purpose:The current clinical strategy to protect the auditory organ against inflammatory damage by migrating leukocytes is the local delivery of glucocorticoids. However, the mechanism by which glucocorticoids confer this protection remains unknown. Therefore, we investigated the cellular and molecular targets of glucocorticoids in the cochlea that could be involved in preventing leukocyte migration. Experimental approach: We used microscopy as well as immunocytochemical and microfluidic techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 47 publications
(106 reference statements)
3
40
0
Order By: Relevance
“…Chem. 31,2012In humans, dexamethasone provides its therapeutic antiinflammatory benefit by acting on specific molecular targets, including the glucocorticoid receptor annexin, prostaglandin endoperoxide synthase 1, and prostaglandin endoperoxide synthase 2 [39][40][41]. Through gene expression analyses, annexin and prostaglandin endoperoxide synthase mRNA have been identified in the ovarian tissue of various fish species, providing evidence of potential involvement of these genes in gonad differentiation and ovulation, respectively [42][43][44].…”
Section: Discussionmentioning
confidence: 97%
“…Chem. 31,2012In humans, dexamethasone provides its therapeutic antiinflammatory benefit by acting on specific molecular targets, including the glucocorticoid receptor annexin, prostaglandin endoperoxide synthase 1, and prostaglandin endoperoxide synthase 2 [39][40][41]. Through gene expression analyses, annexin and prostaglandin endoperoxide synthase mRNA have been identified in the ovarian tissue of various fish species, providing evidence of potential involvement of these genes in gonad differentiation and ovulation, respectively [42][43][44].…”
Section: Discussionmentioning
confidence: 97%
“…The effects of acute elevation of glucocorticoids in the auditory system are most probably mediated by GRs via rapid transcriptional (and possibly non-transcriptional) pathways (Kalinec et al, 2009). One of the mechanisms underlying GR-mediated protection may involve an autoregulation of the receptor.…”
Section: Mechanisms Underlying Glucocorticoid Protection In the Auditmentioning
confidence: 99%
“…In 2009, a completely different role for Hensen cell LDs was proposed by the laboratory of one of the authors of this Review (Kalinec et al, 2009). Experimental evidence indicated that Hensen cell LDs contain significant amounts of the protein annexin A1 (ANXA1), and that glucocorticoids activate a cellular mechanism that results in the release of ANXA1 from the LDs first, and then from the Hensen cells to the extracellular milieu.…”
Section: Early Functional Paradigms For Understanding the Contribumentioning
confidence: 99%
“…Experimental evidence indicated that Hensen cell LDs contain significant amounts of the protein annexin A1 (ANXA1), and that glucocorticoids activate a cellular mechanism that results in the release of ANXA1 from the LDs first, and then from the Hensen cells to the extracellular milieu. Since ANXA1 is known to inhibit leukocyte migration and extravasation by receptor-mediated signaling, as well as to regulate cell death signaling and the phagocytic clearance of apoptotic cells (D'Acquisto et al, 2008), it was proposed that Hensen cell LDs would play a major role in preventing leukocytes from invading the organ of Corti and facilitating the resolution of inflammatory responses in the mammalian inner ear (Kalinec et al, 2009). The potential immunological and anti-inflammatory roles of LDs in the cochlea are discussed in more detail in Section 8.…”
Section: Early Functional Paradigms For Understanding the Contribumentioning
confidence: 99%
See 1 more Smart Citation